Penerapan Data Mining Menganalisa Pola Pembelian Sayur Hidroponik Sawargaloka Hydrofarm Metode Apriori - Dandi Sudrajat; Nur Alamsyah (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to apply an a priori algorithm to determine vegetable purchasing patterns and analyze the results in order to control vegetable stocks at Sawargaloka Hydroponic Hydrofarm. The need for quality and safe food supplies is increasing along with population growth, where plants are grown without using land, but using nutrient solutions that are rich in important substances, the application of data mining using the Apriori method can provide valuable insight into the purchasing patterns of hydroponic vegetables by customers. By understanding these patterns, companies can improve marketing strategies, plan production more efficiently, and provide product recommendations to customers. The results of analytical research using the Apriori method on hydroponic vegetable purchase data at Sawargaloka Hydrofarm, it can be concluded that the application of data mining has great potential in identifying significant purchasing patternsa